OPERAÇÕES DE PREVENÇÃO E COMBATE AOS INCÊNDIOS FLORESTAIS NO ESTADO DE RORAIMA 2003/2004 - Gouveia, Giselle Paes; de Morais, José Carlos Mendes (Floresta, 2004)
A prevenção e o combate aos incêndios florestais nas Unidades de Conservação Federal no estado de Roraima demandaram um sistema de logística e locação de pessoal especializado, além de equipamentos apropriados. O controle de queimadas no Estado em 2003 e 2004 teve início com a elaboração participativa de um calendário de queima, com as seguintes ações do Ibama: o Ibama Itinerante, que emitiu autorizações de queima nos assentamentos, favorecendo a legalização dos produtores sem acesso ao Ibama e o controle deste sobre quanto, onde e o que se queima no Estado; vistorias técnicas associadas à fiscalização especializada, instruindo a queima in locu e o desenvolvimento de atividades típicas de fiscalização. WILDLAND FIRE PREVENTION AND SUPPRESSION IN THE STATE OF RORAIMA 2003/2004 Abstract Prevention and suppression of wildland fires in Federal Conservation Units in the State of Roraima demandeimplementation of a logistical system, work of specialized professionals and the use of appropriate equipments2003 and 2004, the control of burnings in Roraima initiated with the establishment of a calendar for prescburnings elaborated in co-operation with several governmental and non-governmental institutions, with the folloactions being delegated to Ibama: a routing team-work was responsible for the issuing of burning authorizatiosettlements located near to agriculturists, contributing for the legalization of producers without access to Ibamatheir control; the knowledge of who was making a burning, when, where, how much and what areas were burniRoraima; to hold technical inspections associated to law-enforcement activities, instructing small farmers in locuhow to make a prescribed burning, and the development of typical inspection activities.